Technology-assisted Dysgraphic Children Handwriting Model - Rahim, Norsafinar; Husni, Husniza; Jamaludin, Zulikha (Malaysian Journal of Information and Communication Technology (MyJICT), 2020)
Difficulties in handwriting or dysgraphia can have a negative effect on one’s self-esteem and academic achievement in school. This phenomenon is considered a detriment when students have difficulty expressing knowledge through writing; causing extra hardship in mastering all subjects they are learning. Past studies did not deliberate on specific components related to the intervention of dysgraphic students’ handwriting skills development comprehensively, as can be seen in today’s existing handwriting models. Therefore, this study focused on the underlying models of dysgraphic students’involving the main components in the writing process, and the components of ICT support. The principles of modeling with the potential impact of 1) visualization, 2) imagination, and 3) automation in writing need to be considered in addition to the mastery of writing skills. With such a specific model, solutions to these dysgraphic students’ handwriting skill problems can be generalized. Therefore, the main objective of this study was to propose a technology-assisted Dysgraphic Children Handwriting Model (DCHM) to address the problems encountered. This DCHM was validated by four experts – three special education teachers and a paediatric and adolescent psychiatrist. The resulting score was calculated as a percentage value based on the total score obtained for each question. The average percentage for all the criteria evaluated was 91.5%. Overall, all four experts agreed on the key components of the DCHM supported by the ICT component. This study is important for considering handwriting development more holistically and to identify the performance of students’ handwriting in the context of a robust handwriting model.